Immunoregulatory properties of Helicobacter pylori derived molecules - Ogbodo, Ekene N. (2021)
Helicobacter pylori (H. pylori) is a micro-aerophilic, spiral-shaped Gram-negative bacterium which colonises the human stomach of approximately 50% of the population worldwide (1). The infection is asymptomatic in the vast majority of cases, however, about 10-15% result in peptic ulcer disease and 1-2% result in gastric adenocarcinoma. H. pylori prevalence in developed countries is decreasing as the incidence of asthma and allergy is increasing. H. pylori infections are usually established in early childhood when the immune system is developing and at a common age for asthma onset. The infection induces cellular immune responses of types known to inhibit those that drive allergy. Previously, we showed that H. pylori secreted component stimulated CD4+CD25hi regulatory T cells (Tregs) expressing the anti-inflammatory cytokine interleukin-10 (IL-10) more strongly than whole cell lysate. SDS-PAGE was used to resolve the H. pylori and a whole-cell lysate to determine which proteins from the supernatant were enriched and Mass spectrometry (MALDI-TOF) was used to identify the major proteins by peptide mass fingerprinting (PMF). From the result of the MALDI-TOF, vacuolating cytotoxin A (VacA) catalase (KatA), γ- Glutamyl transpeptidase (GGT) and Peptidyl prolyl cis-trans isomerases (PPT) were selected based on the few pieces of evidence of their immunoregulatory abilities, their solubility and potential to be cloned and purified in the past.